Effective equine immunization protocol for production of potent poly-specific antisera against Calloselasma rhodostoma, Cryptelytrops albolabris and Daboia siamensis. - Sompong Sapsutthipas; Poh Kuan Leong; Surasak Akesowan; Ronachai Pratanaphon; Nget Hong Tan; Kavi Ratanabanangkoon (Public Library of Science (PLoS), 2015)
Snake envenomation has been estimated to affect 1.8 million people annually with about 94,000 deaths mostly in poor tropical countries. Specific antivenoms are the only rational and effective therapy for these cases. Efforts are being made to produce effective, affordable and sufficient antivenoms for these victims. The immunization process, which has rarely been described in detail, is one step that needs to be rigorously studied and improved especially with regard to the production of polyspecific antisera. The polyspecific nature of therapeutic antivenom could obviate the need to identify the culprit snake species. The aim of this study was to produce potent polyspecific antisera against 3 medically important vipers of Thailand and its neighboring countries, namely Cryptelytrops albolabris "White lipped pit viper" (CA), Calleoselasma rhodostoma "Malayan pit viper" (CR), and Daboia siamensis "Russell's viper" (DS). Four horses were immunized with a mixture of the 3 viper venoms using the 'low dose, low volume multi-site' immunization protocol. The antisera showed rapid rise in ELISA titers against the 3 venoms and reached plateau at about the 8th week post-immunization. The in vivo neutralization potency (P) of the antisera against CA, CR and DS venoms was 10.40, 2.42 and 0.76 mg/ml, respectively and was much higher than the minimal potency limits set by Queen Soavabha Memorial Institute (QSMI). The corresponding potency values for the QSMI monospecific antisera against CA, CR and DS venoms were 7.28, 3.12 and 1.50 mg/ml, respectively. The polyspecific antisera also effectively neutralized the procoagulant, hemorrhagic, necrotic and nephrotoxic activities of the viper venoms. This effective immunization protocol should be useful in the production of potent polyspecific antisera against snake venoms, and equine antisera against tetanus, diphtheria or rabies.